2014
DOI: 10.1089/tmj.2013.0243
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Interventions for Long-Term Health Management of Chronic Diseases: An Integrative Review

Abstract: However, there are limited smartphone apps for the long-term health management of chronic diseases. More smartphone apps need to be developed to help people manage chronic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
159
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(170 citation statements)
references
References 31 publications
7
159
0
4
Order By: Relevance
“…Similar findings have been reported in studies of symptom-monitoring interventions for other chronic conditions, where patients described feelings of security, felt that they had not been forgotten and were receiving good care outside of hospital and clinic [56]. Additionally, findings of the present review reported that symptom-monitoring and management interventions appeared to improve patient-clinician communication, due to increased and easier access to clinicians and the reduction of patients' uncertainty of whether to contact them.…”
Section: Findings In the Context Of Other Literaturesupporting
confidence: 86%
See 1 more Smart Citation
“…Similar findings have been reported in studies of symptom-monitoring interventions for other chronic conditions, where patients described feelings of security, felt that they had not been forgotten and were receiving good care outside of hospital and clinic [56]. Additionally, findings of the present review reported that symptom-monitoring and management interventions appeared to improve patient-clinician communication, due to increased and easier access to clinicians and the reduction of patients' uncertainty of whether to contact them.…”
Section: Findings In the Context Of Other Literaturesupporting
confidence: 86%
“…These interventions were primarily designed to improve patients' self-management behaviours, such as adherence to treatment and monitoring of their condition [50,51]. The findings of the present review support previous literature that has found mobile technology to be an acceptable platform to deliver interventions to patients with chronic conditions, regardless of the patients' type of disease, age, gender and experience with technology [52][53][54][55][56]. Generally, the majority of patients included in studies of the present review found mobile interventions easy to use and engaging, regardless of the type of device used (e.g.…”
Section: Findings In the Context Of Other Literaturesupporting
confidence: 79%
“…As reviewed elsewhere (Lomborg and Frandsen 2015;Lupton 2016), existing research developed at the intersection of computer science and health studies treats personal self-tracking data as already having predetermined meaning and value, which can be mobilised in order to change the user's behaviour. The concerns in this field of research, therefore, have two key foci when it comes to user-oriented studies: the deployment of self-tracking for improving health through lifestyle interventions (see for example Turner-McGrievy et al 2013;Wang et al 2014); and how self-tracking technologies might be designed to motivate behaviour change on the basis of particular user experiences (see for example Kranza et al 2013)). …”
Section: Personal Data Epistemologiesmentioning
confidence: 99%
“…Meanwhile, use of mobile interactive media, such as smart phones, among students is increasing rapidly owing to the portability and instant accessibility of modern devices. [4] The convenience of mobile internet education enables people to learn anytime and anywhere; the breaking down of the limits of time and space that it represents can be applied to medical education. [5,6]…”
mentioning
confidence: 99%